Vulnerability assessment of water resources – Translating a theoretical concept to an operational framework using systems thinking approach in a changing climate : Case study in Ogallala Aquifer - Kannan, N. (2020)
The overall objective of this study was to develop a novel tool that can translate a theoretical concept (vulnerability of water resources (VWR)) to an operational framework mainly under altered temperature and precipitation, as well as for population change (smaller extent). The developed application was demonstrated in Kansas (overlying the High Plains region/Ogallala Aquifer, considered the “breadbasket of the world”), using 26 indicators with intermediate level of detail. Our results indicate that the western part of the state is vulnerable from agricultural water use and the eastern part from urban water use. The developed tool can be easily replicated to other regions within and outside the US.